2018
DOI: 10.3389/fpsyg.2018.01272
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Prediction Error Theory to Pavlovian Conditioning in an Insect

Abstract: Elucidation of the conditions in which associative learning occurs is a critical issue in neuroscience and comparative psychology. In Pavlovian conditioning in mammals, it is thought that the discrepancy, or error, between the actual reward and the predicted reward determines whether learning occurs. This theory stems from the finding of Kamin’s blocking effect, in which after pairing of a stimulus with an unconditioned stimulus (US), conditioning of a second stimulus is blocked when the two stimuli are presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 61 publications
(109 reference statements)
1
15
0
Order By: Relevance
“…In this study, we investigated whether extended Pavlovian training leads to a change of sensitivity of CR to devaluation of US in the cricket, Gryllus bimaculatus. Crickets are newly emerging animal models for the study of basic mechanisms of learning and memory, because they have excellent learning capabilities and it is relatively easy to apply various experimental manipulations such as pharmacological intervention, RNA interference, and genome editing [14][15][16][17][18][19]. We previously showed that two to four pairing trials to associate an odour with water, with inter-trial intervals (ITIs) of 5 min, are sufficient to lead to protein synthesis-dependent long-term memory that lasts for at least 4 days [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated whether extended Pavlovian training leads to a change of sensitivity of CR to devaluation of US in the cricket, Gryllus bimaculatus. Crickets are newly emerging animal models for the study of basic mechanisms of learning and memory, because they have excellent learning capabilities and it is relatively easy to apply various experimental manipulations such as pharmacological intervention, RNA interference, and genome editing [14][15][16][17][18][19]. We previously showed that two to four pairing trials to associate an odour with water, with inter-trial intervals (ITIs) of 5 min, are sufficient to lead to protein synthesis-dependent long-term memory that lasts for at least 4 days [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Terao et al (2015) observed blocking and a specific case of blocking, "one-trial blocking, " and suggested that Pavlovian conditioning in crickets is best accounted for by the Rescorla and Wagner (1972) model, one of most influential models among error-correction learning theories that are proposed to account for Pavlovian conditioning. Moreover, our pharmacological studies suggested that OA neurons mediate prediction error signals for appetitive conditioning (Terao et al, 2015), whereas DA neurons mediate prediction error signals for aversive conditioning (Terao and Mizunami, 2017;Mizunami et al, 2018), although evidence for the latter is incomplete. These suggestions are comparable to findings in mammals that different types of DA neurons in the midbrain mediate appetitive and aversive prediction error signals, respectively, in Pavlovian conditioning as well as in instrumental conditioning (Schultz, 2013(Schultz, , 2015Engelhard et al, 2019;Gershman and Uchida, 2019).…”
Section: Pavlovian Conditioning In Cricketsmentioning
confidence: 88%
“…What we know about the processes occurring during goal-directed learning in non-human animals supports Dickinson's suggestion. The great evolutionary conservation that we so clearly see in the morphological development of animals is also seen with respect to learning: Associative learning remained grounded in the same basic molecular factors and cybernetic logic we see in slugs, planarians and crickets, which enable prediction-error driven blocking and other behavioral feats (reviewed in Terao, Matsumoto & Mizunami, 2015;Mizunami, Terao & Alvarez, 2018). Going beyond these behaviors requires the evolution of additional dedicated hierarchical structures in the brain: Top layers that integrate and control the information arriving from lowers levels of the hierarchy, and back and forth interactions among layers that enable the formation of associations that involve processes of reentry among groups of neurons in addition to associations between single neurons (Edelman & Gally, 2013;Märtens, Meier, Hillebrand, Tewarie & Van Mieghem, 2017); dedicated memory structures such as the hippocampus and cerebellum in vertebrates that enable the storage of compound representations, as well as flexible, integrating, reward systems.…”
Section: Metacognitive System 1 and System 2 And The Evolution Of Amentioning
confidence: 95%